A theoretical model for bubble coalescence by coupling film drainage with approach processes. (23rd February 2020) - Gong, Shenggao; Gao, Ningning; Han, Luchang; Luo, He'an
Graphical abstract: Highlights: A novel bubble coalescence model has been developed. The initial film thickness and radius were determined based on experimental data. The lubrication form drag force was considered in bubble approach process. The prediction results of novel model were in an agreement with experimental data. Abstract: An improved theoretical model for simulating bubble coalescence caused by turbulence was developed. Unlike the previous models, this improved model simulated the film drainage and approach processes between two bubbles simultaneously in the condition of fully mobile interfaces, considering the influence of the variation of approach velocity, film thickness, film area/radius and interaction forces etc. with time on the bubble coalescence. The lubrication form drag force caused by flattening of colliding surface was introduced to model the approach process. The initial film thickness and radius required for film drainage process were estimated by the expressions validated by experimental data. The critical coalescence velocities for determining coalescence predicted by the improved model were consistent with available experimental data. Moreover, the proposed improved model was used to predict the size distribution in a bubble column, and a good agreement between simulated and experimental results was obtained.